Implementasi Foot Exercise Dalam Manajemen Ketidakstabilan Kadar Glukosa Darah Pada Lansia Dengan Diabetes Melitus: Sebuah Studi Kasus Deskriptif - Sri Hartati; Yeni Elviani; Kamesyworo Kamesyworo; Susmini Susmini; Wahyu Dwi Ari Wibowo (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Introduction: The prevalence of Type 2 Diabetes Mellitus (T2DM) continues to rise significantly among the older adults, leading to various complications if blood glucose levels remain uncontrolled. This study aims to describe the implementation of foot exercise in reducing blood glucose levels among older adults patients with T2DM. Method: A descriptive case study design was employed involving two older adults participants in the Megang Public Health Center work area from March to May 2025. Data were collected through interviews, physical examinations, and blood glucose monitoring using a calibrated glucometer, then analyzed qualitatively through nursing care narratives. The subjects were selected using purposive sampling based on inclusion criteria such as being aged over 60 years and having physical mobility. Result: Results: The result showed that both subjects experienced a consistent decrease in random blood glucose (RBG) levels after each session, with daily reductions ranging from 15 mg/dl to 30 mg/dl. Although individual responses varied due to medication adherence and baseline conditions, both participants demonstrated an overall improvement in glycemic stability. Conclusion: The implementation of foot exercise is an effective non-pharmacological intervention to help lower and stabilize blood glucose levels in older adults patients with Type 2 Diabetes Mellitus.